Regulating nanotechnology: Timely stitch for saving future - Karim, M.E. (2013)
Nanotechnology, the science of using technology at the atomic scale, is the next industrial revolution after internet and is 'the techno buzzword de jour'. Its virtually limitless prospects lure the government, research firms and business ventures around the world to invest huge amount for its commercial application and already hundreds of products containing nanomaterials are available in the market. The United Nations also encouraged the application of nanotechnology in ten priority areas for the benefit of 5 billion people of developing countries within its Millennium Development Goal. Conversely, to many people, it is the next asbestos as it has some serious consequence on environment and health and already seven workers in China got lungs infection and two were died. This is a matter of serious concern that there is no effective regulation both in national or international level to handle the possible environment and human health threats. European countries introduced some voluntary reporting systems which were not successful. In this backdrop, the paper, with an appeal in favour of continuous research and development of nanotechnology, aims to focus on some of the regulatory challenges for the regulators around the world with some suggestions to keep the nanotechnology dream alive avoiding nightmares.